Commemoration of an Epoch: Monuments to the Women’s Suffrage Movement in the United States - Sierra Rooney (Panorama, 2022)

(untitled)
This data-driven analysis unearths monuments that have received little attention, reveals an evolving narrative of the public commemoration of women, and demonstrates how the methods of the digital humanities can enhance the study of art.